HYPNOSIS AND PLACEBOS: RESPONSE EXPECTANCY AS A MEDIATOR OF SUGGESTION EFFECTS - Kirsch, Irving (Anales de Psicología / Annals of Psychology, 1999)
In this paper, data are reviewed indicating that hypnotic and placebo effects share a common mechanism: response expectancy. Placebos and hypnotic procedures may have therapeutic effects because they change the client’s expectations. Both placebo and hypnosis are viewed as instances of the broader phenomenon of suggestion. While other variables may play important roles in the response to suggestions, it remains to be known whether they affect responses by changing expectations or have a direct impact on them. The potential disdvantages of using the idea of trance in therapy are also discussed